2018
DOI: 10.1057/s41253-017-0053-6
|View full text |Cite
|
Sign up to set email alerts
|

Post-democracy and institutionalized austerity in France: budgetary politics during François Hollande’s presidency

Abstract: This paper applies the concept of post-democracy coined by Crouch to shed light on the emerging political dynamics of macroeconomic policy coordination in the Eurozone as they applied to France during Hollande's presidency. Firstly, the paper explains the nature of EMU reform, characterized here as post-democratic by institutional design, before analysing its impact on France's budgetary politics. Finally, the French case involving Hollande's balancing act between supranational rules and domestic spending pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…In turn, the lack of internal and ideological cohesiveness were conducive to the historical collapse of the Socialist party in the 2017 presidential elections (Lefebvre 2017). Beyond partisan consequences, our observations are also consistent with the "post-democracy" theoretical framework, which emphasises that political change between centre left and centre-right parties does not lead to different economic policies (Crouch 2004, Streeck & Schäffer 2013, Glencross 2018. These authors also claim that this lack of change weakens voter turn-out, which was observed in the 2017 elections (Braconnier et al 2017).…”
Section: Feedback Loopssupporting
confidence: 87%
“…In turn, the lack of internal and ideological cohesiveness were conducive to the historical collapse of the Socialist party in the 2017 presidential elections (Lefebvre 2017). Beyond partisan consequences, our observations are also consistent with the "post-democracy" theoretical framework, which emphasises that political change between centre left and centre-right parties does not lead to different economic policies (Crouch 2004, Streeck & Schäffer 2013, Glencross 2018. These authors also claim that this lack of change weakens voter turn-out, which was observed in the 2017 elections (Braconnier et al 2017).…”
Section: Feedback Loopssupporting
confidence: 87%
“…The response to the health crisis has been an opportunity to highlight the strong need for commitment from the various budget actors and decision-makers relative to each other at various levels. First, despite the European involvement and its flexibility, there is a long-term risk of high indebtedness for France, which could push future policies toward greater French budgetary responses to COVID-19 austerity than after the Great Recession (Glencross, 2018;House et al, 2020;Math, 2017) and make France more vulnerable to future pandemics. Second, we observed the rise of participatory budgets in local communities in response to the centralization that characterizes France, which calls for higher involvement and engagement from citizens, and ultimately decentralization.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of the sanctioning mechanisms, whether pre or post overhaul, remain unseen as sanctions for the undesired excesses have never been imposed. The corrective arm continues to be politically driven (European Fiscal Board 2019) and avoiding penalties is often linked with factors like the country's negotiating capacities or the so-called 'unexpected adverse economic events' (Glencross 2018). Despite failing to impose sanctions and thus possibly affecting its credibility, the EDP has indirect effects on the MS.…”
Section: Supranational Rules On Public Financesmentioning
confidence: 99%